Prediksi Spasial Wilayah Resiko Tanah Longsor Di Jawa Tengah Berdasarkan SAVI, OSAVI, DVI, NDVI Menggunakan Krigging - Dwi Hayati; Sri Yulianto Joko Prasetyo (Indonesian Journal of Computing and Modeling, 2018)
Landslides are the process of moving rock periods (soil) due to gravity. On the spatial prediction of landslide occurrence in the District in Central Java based on vegetation index using kriging. The vegetation index is the amount of green vegetation values obtained from the processing of digital signal data of the brightness value of several satellite sensor data channels. Some of the vegetation index algorithms used are SAVI (Soil Adjusted Vegetation Index), OSAVI (Optimized Soil Adjusted Vegetation Index), DVI (Difference Vegetation Index), NDVI (Normalized Difference Vegetation Index). Kriging is one of the prediction and interpolation methods in geostatistika, consisting of two types of ordinary kriging when only one variable and cokriging when there are more than one variable observed. Kriging functioning formation of color gradient pattern on map result of data interpolation. In this research it was found that the occurrence of landslide in the sample area correlated with low, medium, high, DVI vegetation index of DVI, NDVI, SAVI, OSVII. Banjarnegara Regency is prone to landslides in medium category, Wonosobo Regency in High category, Magelang Regency in High category, Kebumen Regency in Low category, Purworejo Regency in Low category. So it can be concluded that landslides are affected or associated with low tree cover seen by NDVI, DVI, SAVI, OSAVI vegetation indices.